Effects of intermittent ractopamine HCl (paylean1) use on pig growth performance in late finishing - Neill, C.R.; Groesbeck, C.N.; Brown, K.R.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 324 pigs (initially 149 lb) were used in a 56-d feeding trial to examine growth performance of pigs as affected by different ractopamine HCl (Paylean) regimens. There were four experimental treatments: A) the control diet fed for 56 d; B) the Paylean diet (9 g/ton) fed for 21 d, then control for 35 d; C) Paylean fed for 21 d, then control for 14 d, and then Paylean for 21 d; and D) control diet 35 d and then Paylean 21 d. Treatment C (feeding Paylean for 21 d, withdrawing it for 14 d, and re-feeding for 21 d) had the same overall affect on ADG and F/G as feeding Paylean for the last 21 d only. Weight gain was greater (P<0.008) for the pigs in Treatments C and D, which fed Paylean for the last 21 d, compared with that of control pigs or those fed Paylean for the initial 21 d of the study only. Pigs fed Paylean and then had it withdrawn had decreased (P>0.46) ADG and F/G, compared with pigs not previously fed Paylean. These results suggest that withdrawing Paylean for 14 d and re-feeding will have the same overall growth effect as feeding Paylean once.
Swine research, 2005 is known as Swine day, 2005
Keywords: Finishing pig; Paylean; Withdrawal; Swine